Soybean ubiquitous urease with purification facilitator: An addition to the moonlighting studies toolbox. (February 2017) - Martinelli, Anne H.S.; Lopes, Fernanda C.; Broll, Valquiria; Defferrari, Marina S.; Ligabue-Braun, Rodrigo; Kappaun, Karine; Tichota, Deise M.; Fruttero, Leonardo L.; Moyetta, Natalia R.; Demartini, Diogo R.; Postal, Melissa; Medeiros-Silva, Monica; et al.
Graphical abstract: Highlights: Soybean Ubiquitous Urease fused to GST (uSBU-GST) displays antifungal properties. GST-uSBU interferes with fungal secondary metabolism. The recombinant urease induces the formation of pseudo-hyphae in yeasts. The fusion protein possess insecticidal activity and aggregates hemocytes. GST-uSBU is an adequate model to study biological properties of ureases. Abstract: Ureases are nickel-dependent enzymes that catalyze the hydrolysis of urea to ammonia and carbon dioxide. In soybean ( Glycine max ), the embryo-specific urease (eSBU), the ubiquitous urease (uSBU), and a third isoform (SBU-III) are synthesized. Our group has previously demonstrated that eSBU, purified from seeds, has antifungal properties against phytopathogenic fungi, entomotoxicity against Dysdercus peruvianus, the ability to induce blood platelet aggregation, and these properties are independent of its enzymatic activity. Here we describe the biological properties of apo-uSBU fused to glutathione S-transferase (GST) produced in Escherichia coli . Removal of GST affected apo-uSBU stability. We performed a Response Surface Methodology to optimize GST-uSBU production to 5 mg per liter and then bioassays were carried out. The recombinant protein exhibited inhibitory effects on filamentous fungi and affected fungal secondary metabolism. Candida albicans and C. tropicalis were also susceptible to GST-uSBU and formed pseudo-hyphae. The fusion protein was toxic against Rhodnius prolixus, with the toxicity being accompanied by in vivo and in vitro hemocyte aggregation. Rabbit platelet also aggregated in the presence of GST-uSBU. Thus, uSBU displayed similar biological properties as previously described for eSBU even when fused to GST, reinforcing the proposed role of ureases in plant defense.